Pollen-pistil interaction and asymmetric reproductive interference in Veronica species - Sachiko Nishida; Naoko Watanabe; Keisuke Hashimoto; Yuyan Zhang; Ko-Ichi Takakura; Masahiro M. Kanaoka (Journal of Plant Research, 2026)

Sensitivity assessment of diphacinone by pharmacokinetic analysis in invasive black rats in the Bonin (Ogasawara) Archipelago, Japan - Kazuki Takeda; Keita Shimizu; Miyu Sato; Masafumi Katayama; Shouta M.M. Nakayama; Kotaro Tanaka; Yoshinori Ikenaka; Takuma Hashimoto; Ryuichi Minato; Yusuke Oyamada; Kazuyuki D. Tanaka; Goro Kimura; et al. (Pesticide Biochemistry and Physiology, 2024)

Responsibility for sustainable water consumption in the global supply chains - Masaharu Motoshita; Stephan Pfister; Takahiro Sasaki; Keisuke Nansai; Seiji Hashimoto; Ryosuke Yokoi; Kamrul Islam; Matthias Finkbeiner (Resources, Conservation and Recycling, 2023)

Therapeutic effects of anti-amyloid β antibody after intravenous injection and efficient nose-to-brain delivery in Alzheimer’s disease mouse model - Noriyasu Kamei; Ayaka Hashimoto; Erina Tanaka; Kaho Murata; Maika Yamaguchi; Natsuki Yokoyama; Masahiro Kato; Keisuke Oki; Takashi Saito; Takaomi C. Saido; Mariko Takeda-Morishita (Drug Delivery and Translational Research, 2022)

Brain 5-HT2A receptor binding and its neural network related to behavioral inhibition system - Kazuho Kojima; Shigeki Hirano; Yasuyuki Kimura; Chie Seki; Yoko Ikoma; Keisuke Takahata; Takehito Ito; Keita Yokokawa; Hiroki Hashimoto; Kazunori Kawamura; Ming-Rong Zhang; Hiroshi Ito; et al. (Brain Imaging and Behavior, 2022)
The tendency to avoid punishment, called behavioral inhibition system, is an essential aspect of motivational behavior. Behavioral inhibition system is related to negative affect, such as anxiety, depression and pain, but its neural basis has not yet been clarified. To clarify the association between individual variations in behavioral inhibition system and brain 5-HT 2A receptor availability and specify which brain networks were involved in healthy male subjects, using [ 18 F]altanserin positron emission tomography and resting-state functional magnetic resonance imaging. Behavioral inhibition system score negatively correlated with 5-HT 2A receptor availability in anterior cingulate cortex. A statistical model indicated that the behavioral inhibition system score was associated with 5-HT 2A receptor availability, which was mediated by the functional connectivity between anterior cingulate cortex and left middle frontal gyrus, both of which involved in the cognitive control of negative information processing. Individuals with high behavioral inhibition system displays low 5-HT 2A receptor availability in anterior cingulate cortex and this cognitive control network links with prefrontal-cingulate integrity. These findings have implications for underlying the serotonergic basis of physiologies in aversion.

Comparisons among populations and individuals to evaluate pollen–pistil interaction as a mechanism of reproductive interference in Taraxacum - Keisuke Hashimoto; Akane Yamamoto; Masahiro M. Kanaoka; Akiyo Naiki; Ko-Ichi Takakura; Sachiko Nishida (Journal of Plant Research, 2022)

EcoBalance 2016-responsible value chains for sustainability (October 3-6, 2016, Kyoto, Japan) - Keisuke Nansai; Masaharu Motoshita; Ichiro Daigo; Seiji Hashimoto; Kiyotada Hayashi; Keiichiro Kanemoto; Aiichiro Kashiwagi; Yoshinori Kobayashi; Shinsuke Kondo; Yuki Kudoh; Yasunari Matsuno; Hiroki Tanikawa; et al. (The International Journal of Life Cycle Assessment, 2017)

Variation in the strength of reproductive interference from an alien congener to a native species in Taraxacum - Sachiko Nishida; Keisuke Hashimoto; Masahiro M. Kanaoka; Ko-Ichi Takakura; Takayoshi Nishida (Journal of Plant Research, 2017)

Physicochemical and Pharmacokinetic Characterization of Amorphous Solid Dispersion of Meloxicam with Enhanced Dissolution Property and Storage Stability - Masanori Ochi; Keisuke Kimura; Atsushi Kanda; Takaki Kawachi; Akitoshi Matsuda; Kayo Yuminoki; Naofumi Hashimoto (AAPS PharmSciTech, 2016)

Serotonin 5-HT7 Receptor Blockade Reverses Behavioral Abnormalities in PACAP-Deficient Mice and Receptor Activation Promotes Neurite Extension in Primary Embryonic Hippocampal Neurons - Minako Tajiri; Atsuko Hayata-Takano; Kaoru Seiriki; Katsuya Ogata; Keisuke Hazama; Norihito Shintani; Akemichi Baba; Hitoshi Hashimoto (Journal of Molecular Neuroscience, 2012)

9th International Conference on EcoBalance (9th ICEB)—towards and beyond 2020, November 9–12, 2010, Tokyo, Japan - Keisuke Nansai; Yuki Kudoh; Hiroki Hondo; Kiyotada Hayashi; Kazuyo Matsubae; Kenichi Nakajima; Shinsuke Murakami; Masaharu Motoshita; Seiji Hashimoto; Minako Hara; Michiyasu Nakajima; Rokuta Inaba; et al. (The International Journal of Life Cycle Assessment, 2011)

Neuroprotective Effect of PACAP Against NMDA-Induced Retinal Damage in the Mouse - Kimi Endo; Tomoya Nakamachi; Tamotsu Seki; Nobuyuki Kagami; Yoshihiro Wada; Keisuke Nakamura; Koji Kishimoto; Motohide Hori; Daisuke Tsuchikawa; Norihito Shinntani; Hitoshi Hashimoto; Akemichi Baba; et al. (Journal of Molecular Neuroscience, 2011)

What Factors Have Changed Japanese Resource Productivity? - Seiji Hashimoto; Shigekazu Matsui; Yu Matsuno; Keisuke Nansai; Shinsuke Murakami; Yuichi Moriguchi (Journal of Industrial Ecology, 2008)
Summary In 2003, the Fundamental Plan for Establishing a Sound Material‐Cycle Society was developed; it established indicators and numerical targets for each of three aspects of material flows in Japan. One of the three indicators is resource productivity: Gross domestic product divided by direct material input (GDP/DMI). This article elucidates factors that have changed recent resource‐use intensity (the inverse of resource productivity) in Japan. Specifically, the analysis emphasizes decomposing resource‐use intensity into the factors of recycling, induced material‐use intensity, demand structure, and average propensity to import. Conclusions drawn from analyses of data from the 1995–2002 period are as follows: (1) Changes in the structure of demand (i.e., the magnitude of the demand for a particular set of goods and services relative to total demand) produced the largest contribution to a reduction in resource‐use intensity. In addition, the aggregate of the decline in induced material‐use intensity and the improvement in recycling contributed as much as changes in the demand structure. (2) Final demand for construction declined steadily during the study period, resulting in the largest contribution to the decline in resource‐use intensity. (3) Final demand for machinery and services increased, whereas their induced material‐use intensity declined, contributing to the decline in resource‐use intensity as a whole. (4) Although the effects of recycling are not great, the increased recycling of nonmetallic minerals contributed to the decline in resource‐use intensity.

Modeling interactions between photic and nonphotic entrainment mechanisms in transmeridian flights - Mitsuyuki Nakao; Keisuke Yamamoto; Ken-ichi Honma; Satoko Hashimoto; Sato Honma; Norihiro Katayama; Mitsuaki Yamamoto (Biological Cybernetics, 2004)

Simulating transmeridian flights - Mitsuyuki NAKAO; Keisuke YAMAMOTO; Ken-ichi HONMA; Satoko HASHIMOTO; Sato HONMA; Norihiro KATAYAMA; Mitsuaki YAMAMOTO (Sleep and Biological Rhythms, 2004)

Upregulation of redox-regulating protein, thioredoxin, in endomyocardial biopsy samples of patients with myocarditis and cardiomyopathies - Masaomi Nimata; Chiharu Kishimoto; Keisuke Shioji; Katsumi Ishizaki; Shoji Kitaguchi; Tetsuo Hashimoto; Norikazu Nagata; Chuichi Kawai (Molecular and Cellular Biochemistry, 2003)